The Effect of Internet of Things (IoT) and CEISA 4.0 System Reliability on Logistics Company Performance: The Mediating Role of Service Quality in Freight Forwarding Companies in Jakarta - Jusuf Roni Siahaan; Siti Maemunah; Sofwan Farisyi; Eduard Alfian Syamsya; Rohana Sitanggang (Siber Journal of Transportation and Logistics, 2026)
This study analyzes the effect of Internet of Things (IoT) and CEISA 4.0 system reliability on logistics company performance, with service quality as a mediating variable in freight forwarding companies in Jakarta. A quantitative approach was applied using data from 288 CEISA 4.0 users, analyzed through SEM-PLS. The results show that IoT has a significant positive effect on both service quality and company performance. Meanwhile, CEISA 4.0 reliability has no significant direct effect on company performance but positively affects service quality. Furthermore, service quality mediates the relationship between IoT and company performance but does not mediate the effect of CEISA 4.0 reliability. These findings indicate that IoT plays a more critical role in improving logistics performance, while the effectiveness of CEISA 4.0 is still limited. Therefore, improving system reliability and service quality is essential to enhance company performance in the logistics sector.